Prasugrel Reduces Agonists′ Inducible Platelet Activation and Leukocyte–Platelet Interaction more efficiently than Clopidogrel. Issue 5 (12th September 2013) - Gremmel, Thomas; Eslam, Roza Badr; Koppensteiner, Renate; Lang, Irene M.; Panzer, Simon
Summary: Aims: The antiplatelet effects of clopidogrel and prasugrel have mainly been compared using different platelet reactivity tests. Further, data on the impact of both drugs on thrombin‐inducible platelet activation are scarce. We therefore investigated the influence of clopidogrel and prasugrel on different flow cytometric parameters of platelet activation as well as on platelet function assessed by leukocyte–platelet interaction. Methods: Baseline, ADP and thrombin receptor‐activating peptide (TRAP)‐6 inducible P‐selectin expression, activation of glycoprotein (GP) IIb/IIIa and monocyte–platelet aggregate (MPA) formation were determined by flow cytometry in 84 clopidogrel‐ and 21 prasugrel‐treated patients undergoing percutaneous coronary intervention with stent implantation. Results: Baseline expressions of P‐selectin and activated GPIIb/IIIa did not differ significantly between clopidogrel‐ and prasugrel‐treated patients (both P  > 0.2). After activation with ADP or TRAP‐6, patients with clopidogrel therapy exhibited significantly higher platelet surface expressions of P‐selectin and activated GPIIb/IIIa than prasugrel‐treated patients (all P  ≤ 0.001). Further, high P‐selectin and high GPIIb/IIIa were significantly more frequent in clopidogrel‐treated patients than in patients on prasugrel therapy (all P  = 0.01). Likewise, the formation of MPA without addition of agonists did not differ significantly between patients receiving clopidogrel and patients on prasugrel therapy ( P  = 0.2). After activation with ADP or TRAP‐6, clopidogrel‐treated patients showed a significantly more pronounced formation of MPA than patients‐receiving prasugrel (both P  = 0.02). Conclusions: Prasugrel reduces ADP and TRAP‐6 inducible platelet activation, and leukocyte–platelet interaction more efficiently than clopidogrel.